2001
DOI: 10.1200/jco.2001.19.4.1147
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Comorbidity and Cancer in Older Patients: Approaches to Expand the Knowledge Base

Abstract: Not only do persons 65 years and older bear a disproportionate burden of cancer, advancing age is associated with increased vulnerability to other age-related health problems. Newly diagnosed older cancer patients who have lived into later years of life may have concurrent ailments (eg, diabetes, chronic obstructive pulmonary disease, heart disease, arthritis, and/or hypertension) that could affect treatment choice, prognosis, and survival. The clinician must often make cancer treatment decisions in the contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
137
0
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(145 citation statements)
references
References 8 publications
4
137
0
4
Order By: Relevance
“…27 Because of comorbidities, older patients may have more difficult treatments and may face additional barriers, such as memory impairment, language deficits, and lack of transportation to the clinic. [27][28][29] Thus, patient navigation may be more effective in older patients because it aims to overcome barriers specific to this population. Older women may face barriers associated with scheduling appointments in a timely manner following diagnosis, perhaps due to a lack of understanding of the cancer care process.…”
Section: Discussionmentioning
confidence: 99%
“…27 Because of comorbidities, older patients may have more difficult treatments and may face additional barriers, such as memory impairment, language deficits, and lack of transportation to the clinic. [27][28][29] Thus, patient navigation may be more effective in older patients because it aims to overcome barriers specific to this population. Older women may face barriers associated with scheduling appointments in a timely manner following diagnosis, perhaps due to a lack of understanding of the cancer care process.…”
Section: Discussionmentioning
confidence: 99%
“…Such adverse alterations in body composition aggravates the age-related loss of muscle mass (termed sarcopenia), which can further compromise muscle strength, physical function and independent living, particularly in older patients who may be approaching thresholds for disability. 10,11 Further, older prostate cancer patients are normally already at a greater risk for other comorbid conditions and physical limitations (for example, cardiovascular disease, diabetes, osteoporosis, skeletal fractures) 11,12 that can dramatically affect their muscle and physical function. However, the development of effective counter strategies requires a detailed understanding of the consequences of AST on physical adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…in obese children with acute myeloid leukaemia (AML) [32]. Meloni et al [33] found delayed granulocyte recovery and Although DM seems to be a strong independent factor influencing mortality of patients with malignancies [34][35], there are only a few observations about an increased myelotoxicity during chemotherapy. Srokowsky et al [36] demonstrated in elderly breast cancer patients that diabetic patients were more likely to experience toxicities of chemotherapy than were non-diabetic patients.…”
Section: Discussionmentioning
confidence: 99%